Highly-stable, bifunctional, binder-free & stand-alone photoelectrode (FexNi1-xO@a-CC) for natural waters splitting into hydrogen. (15th October 2022) - Yousaf, Maryam; Ahmad, Muhammad; Batool, Aisha; Zhao, Zhi-Ping
Abstract: Photoelectrochemical (PEC) water splitting is a promising approach to boost green hydrogen production. Herein, we prepared novel binder-free photoelectrode by direct growth of iron doped nickel oxide catalyst over activated carbon cloth (Fex Ni1-x O@a-CC) having band gap energy of 2.2 eV for overall water splitting. Fex Ni1-x O@a-CC photoelectrode had shown remarkable lower potential of only 1.36 V for oxygen evolution reaction (OER) to reach 10 mA cm −2 current density using very low photonic intensity of 8.36 × 10 −4  E/L.s. For the first time, we also reported electrical efficiency required for PEC water splitting for 1 m 3 of water that is equal to 0.09 kWh/m 3 . Fex Ni1-x O@a-CC photoelectrode also exhibits low potentials of 1.44 V (OER) and −0.210 V (HER) at 10 mA cm −2 to split sea water. Our results confirmed that designing Fex Ni1-x O@a-CC photoelectrode would be an innovative step to widen green energy conversion applications using natural waters (both sea and fresh water). Graphical abstract: Image 1 Highlights: Polymer binders covered up active sites of powder catalysts & increase overpotential. Bifunctional, binder-free and stand-alone electrode (Fex Ni1-x O@a-CC) was developed. Electrode required 8.36 × 10 −4  E/(L.s) photonic intensity to produce H2 . For 1 m 3 water splitting, Fex Ni1-x O@a-CC consumed EE of 0.09 kWh/m 3 (visible range). Photoelectrode Fex Ni1-x O@a-CC split sea water without chlorine evolution reaction.